Pendampingan dan Peningkatan Profesional Guru Bahasa Inggris melalui Aplikasi Modul E-Learning di SMU 1 Nan Sabaris - Yosa Novia Dewi; Kristian Burhan; Indri Astuti; Eka Melati; Zefriyenni Zefriyenni (Jurnal Abdimas Adpi Sosial dan Humaniora, 2021)
One way to increase teacher professional development is through the provision of quality learning media, namely E-learning or Internet learning because it is a medium that can improve the quality of education. The purpose of this workshop is to be able to add new knowledge and experience for teacher in the implementation of learning methods, to be able to use the internet in the learning process and to be able to modify learning methods by utilizing information technology facilities as an effort to develop professional teachers. The method used starts from the planning stage, implementation to the evaluation stage. The workshop was carried out for two days. The first day is more focused on providing material while the second day is more focused on the practice of using e- learning module application technology. The workshop participants were very enthusiastic during the activity.